Empirical Study on Public High School System in Vietnam: Post Doi Moi - Nam, Tran Duy; Viet, Ha Thanh (European Scientific Journal, ESJ, 2017)
The system of education in Vietnam is administered by the Ministry of Education and Training (MOET), and it is a broad system of state-run schools for students from about four years of age to high school age. The educational system comprises of five classes: kindergarten, primary, secondary, upper-optional (additionally alluded to as secondary school), and college level, with broadly managed exit and selection tests between each. The principal motivation behind this study is to analyze the connection between pre-secondary school factors, school condition, school structure, collective duty, scholarly optimism with the scholastic performance of the public high school students in Vietnam. SPSS analysis shows that only two variables can be a significant indicator of academic performance, that are school environment (B= -1.369, t=51.356, p<0.01) and pre-high school factor (B=-.384, t= -13.947, p<0.01) while school structure, collective responsibility, and academic optimism have found to be insignificant indicator of academic performance as compared to the other two variables in a multivariate context although, during the bivariate analysis, academic optimism had been found to be significantly related to academic performance. School environment was also found to have higher ‘B’ value compared to pre-high school factor. Hence, this study suggests that among all the independent variables studied, school environment gave the most effective towards the academic performance of students in the public high school of Vietnam.